Інформаційні технології для інноваційного інжинірингу - Краскевич, В.Є.; Селіванова, А.В. (Математичне моделювання в економіці, 2018)
Проаналізовано інформаційні інструменти для підтримки інноваційної діяльності. Розкрито поняття та особливості краудфандингових платформ. Проаналізовано перспективи розвитку краудфандингу в Україні. Проанализировано информационные инструменты для поддержки инновационной деятельности. Раскрыто понятия и особенности краудфандинговых платформ. Проанализировано перспективы развития краудфандинговых платформ в Украине. The aim of article to analyze the advanced world experience with crowdfunding platform for startups and prospects of innovation activity in Ukraine. Crowdfunding is an effective means of raising funds for the implementation of various projects. It can be both cultural and social projects and technical. As an information tool for fundraising crowdfunding platform is a specialized site for placement of innovative ideas. The platform provides financial and legal aspects of interaction and helps participants.